PRAKTIK MONOPOLI PERDAGANGAN DAN IKHTIKAR DALAM PERSPEKTIF EKONOMI SYARIAH - Ali Bawafie, Aniq Akhmad; Kara, Muslimin; Wahyuddin Abdullah, Muhammad; Bukhari, Bukhari; Zikri Dwiatmaja, Ahmad (Prodi Hukum Ekonomi Syariah, STI Syariah AL-Hilal SIgli, 2024)
A monopoly is a less competitive type of market where there is no direct business competition. In a competitive market, equilibrium is reached when supply and demand meet at a mutually agreed price and quantity between seller and buyer. Both parties benefit from this transaction, and no losses are incurred as a consequence of the exchange.This research was conducted using a qualitative approach based on desk research. When analysed thoroughly, ikhtikar is not always the same as monopoly or hoarding. In the Islamic context, every individual has the right to engage in business, whether as the sole seller (or producer) in the market. Not all acts of hoarding can be termed as monopoly. The prohibition only applies if the monopolist controls a good with inelastic demand elasticity. A monopolist who controls a good with an elastic demand elasticity will suffer losses.